Morphometric Variations of Rasbora Group (Pisces: Cyprinidae) in Lake Laut Tawar, Aceh Province, Indonesia, Based on Truss Character Analysis - ZAINAL ABIDIN MUCHLISIN (HAYATI Journal of Biosciences, 2013)
The genetic variation of Rasbora group in Lake Laut Tawar has been reported previously, however information on morphometric variations of this Genus was not available. Hence, the objective of the present study was to evaluate the morphometric characters of Rasbora group in Lake Laut Tawar, in order to contribute useful information on the biology of this important fish. The truss morphometric method was utilized in this study. A total of 45 samples of Depik, 42 samples of Eas and 44 samples of Relo were used in this evaluation. Eight homologous landmarks were determined along the outline of the fish, and based on these landmarks, 14 characters or linear measurements were recognized. Discriminant function analysis was employed to distinguish the fish sample. The results showed that the truss morphological characters could highlight the high differentiation between Relo and the other two groups, and the closeness of Eas and Depik. The morphometric data strongly indicated that Eas and Depik should be regarded as a same species, Rasbora tawarensis, and Relo may be considered as a cryptic species. This finding is in agreement to the genetic data  which was published previously.